Tidal energy device hydrodynamics in non-uniform transient flows - JOHN CHAPMAN (2008)
Tidal energy devices convert the flow of water induced by the tidal cycle into useful energy. Presently the most common type of tidal energy device is a horizontal axis zero head turbine. Conceptually the form of these devices is similar to modern wind turbine systems. This thesis presents the development of a flexible code that models the hydrodynamic behaviour of a tidal stream turbine rotor and its supporting structure in a non-uniform, time varying flow. Blade Element Momentum Theory (BEMT) is reviewed and its implementation is discussed. Corrections to the theory are reviewed in the context of operation in an ocean environment. The completed model operates in a three-dimensional representation of the ocean and includes the calculation of supporting structure loads using Morison's equation. The flow regime either includes boundary layer effects and a calculated wave climate or can be taken from data measured with an ADCP. Specific model features are introduced that allow realistic appraisal of the system's performance and load regime as well as specific situations such as braking of the rotor. The capability of the code is then demonstrated using a non-uniform, time varying flow and the importance of this in the design of turbine systems is discussed. The novel features introduced in this thesis are; the inclusion of non rotor-normal inflow in the BEMT equations, a new, robust approach to solving the BEMT equations and a novel blade-off modelling approach. A calibrated marine tower shadow model, a novel procedure for comparing the performance of alternative device concepts and a method to input ADCP data directly to the model system were also novel steps introduced in the thesis.